2017
DOI: 10.1136/vr.104028
|View full text |Cite
|
Sign up to set email alerts
|

Alternative methods to compare safety of live‐attenuated respiratory Newcastle disease vaccines in young chicks

Abstract: The work reported here is an initial attempt to find an alternative method by which the safety of live-attenuated Newcastle disease virus (NDV) vaccines for the respiratory tract of young chickens can be assessed. The current recommended methods involve either the subjective assessment of respiratory signs, or raise ethical concerns, as in the case of the intracerebral pathogenicity index. The two methods considered here were the use of tracheal organ cultures to assess the level of ciliostasis which the vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The lack of ciliostasis observed in NDV B1-infected positive controls contrasts with previous reports demonstrating that NDV caused ciliostasis in tracheal explants. Butler, et al [40] demonstrated that NDV caused ciliostasis within 2 to 6 days after infection of tracheal explants, and Malo, et al [41] reported that following vaccination of one-day-old chicks with lentogenic NDV, the peak of ciliostasis occurred at 5 and 7 dpv and waned by 13 dpv. The discrepancy between our results and the previous studies may be explained by the use of a different lentogenic NDV strain; B1 in our studies and LaSota in previous reports [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of ciliostasis observed in NDV B1-infected positive controls contrasts with previous reports demonstrating that NDV caused ciliostasis in tracheal explants. Butler, et al [40] demonstrated that NDV caused ciliostasis within 2 to 6 days after infection of tracheal explants, and Malo, et al [41] reported that following vaccination of one-day-old chicks with lentogenic NDV, the peak of ciliostasis occurred at 5 and 7 dpv and waned by 13 dpv. The discrepancy between our results and the previous studies may be explained by the use of a different lentogenic NDV strain; B1 in our studies and LaSota in previous reports [41].…”
Section: Discussionmentioning
confidence: 99%
“…Butler, et al [40] demonstrated that NDV caused ciliostasis within 2 to 6 days after infection of tracheal explants, and Malo, et al [41] reported that following vaccination of one-day-old chicks with lentogenic NDV, the peak of ciliostasis occurred at 5 and 7 dpv and waned by 13 dpv. The discrepancy between our results and the previous studies may be explained by the use of a different lentogenic NDV strain; B1 in our studies and LaSota in previous reports [41]. It is well established that the LaSota vaccine strain is more virulent than B1 [42], which may explain the ciliostasis observed in LaSota-vaccinated chicks or LaSota-infected tracheal explants, whereas ciliostasis was not observed in our study using B1 vaccine.…”
Section: Discussionmentioning
confidence: 99%